Marketing and online advertisement: An overview of legal implication in Malaysia - Ayub, Zainal Amin; Mohamed Yusoff, Zuryati; Halim, Fairol (Universiti Malaysia Sarawak, 2009)
In the era of digital world, and so with marketing, online advertisement over the Internet is rampant and pertinent in marketing product and services, be it business to business (B2B) or business to consumer (B2C).However, the raging use of Internet to market the product and services with advertisement leads to number of legal issues put into test, to name a few, authenticity, confidentiality, integrity and non-repudiation.The issue of non-repudiation relates directly to the issue of online advertisement, whether it is an “offer” or an “invitation to treat”, since if it is an offer, the seller cannot repudiate the acceptance made by the buyer over the online advertisement. This article will discuss this prevalent issue which is yet to be decided by the Malaysian judicial system.